Molecularly doped electrophosphorescent solution processed and laser patterned emitters for devices - Kim, Mu-Hyun; Suh, Min Chul; Kwon, Jang Hyuk; Chin, Byung Doo (ELSEVIER SCIENCE SA, 2007)
We have fabricated highly efficient, molecularly doped green electrophosphorescent devices in which the emitter layer was comprised of a small molecule and polymeric co-host system. The polymeric hosts were evaluated not only in terms of achieving efficient device performance without triplet quenching, but also in terms of film formation ability and donor-to-acceptor transfer quality by laser thermal patterning. 4,4'-N,N'-dicarbazole-biphenyl (CBP) or 2-4(biphenylyl)-5-(4-tert-butylphenyl)-1,3,4-oxadiaxole (PBD) was used as small molecule, in combination with the selected co-host polymeric host, poly(9-vinyl carbazole) (PVK). Stripe patterns with edge roughnesses less than 3 mu m and device performance equal to that of spin-coated devices were achieved. The soluble, patterned electrophosphorescent device developed in the present work can be used as the basis for the future development of high efficiency, large area organic light emitting devices. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: LIGHT-EMITTING DEVICES; POLYMERS; DIODES; POLY(N-VINYLCARBAZOLE); LEDS